Pengaruh pembiayaan Mudharabah,Murabahah dan Musyarakah Terhadap Bank Umum Syariah dengan NPF sebagai Variabel Moderasi - Lutfiana Mayang Febrianti; Mochamad Fariz Irianto; Doni Wirshandono (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The research conducted analyzes the impact of Mudharabah, Murabahah and Musyarakah financing on the profitability of Islamic commercial banks during the period from 2016 to 2020. In this analysis, NPF was used as a moderating variable. Quantitative methods were adopted to analyze monthly time series data from 2016 to 2020, which was accessed via the OJK statistical database. The sample selection process was purposive sampling, referring to certain criteria, with a total of 120 samples examined over the five years. This research uses multiple linear regression analysis method which is conducted through SPSS application to process the data. This research helps to highlight factor affecting the Financial Perfomance of Islamic Banks. The findings of this research can provide valuable information to decision makers in Islamic banks to design more optimal financing strategies and improve credit risk management through a deeper Understanding the relationship between financing and profitability.. The results of this analysis show a significant positive influence between Mudharabah, Murabahah and Musyarakah financing on profitability, which mainly affects ROA in Sharia commercial banks. Although NPF does not significantly moderate the relationship between Mudharabah and ROA, this research reveals the important role of NPF in moderating the impact of Murabahah and Musyarakah financing on ROA.